2010
DOI: 10.3897/compcytogen.v4i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical karyotypic variation of Rhinophylla fischerae (Chiroptera: Phyllostomidae) suggests the occurrence of cryptic species

Abstract: Abstract. The genus Rhinophylla Peters, 1865 (Carolliinae: Phyllostomidae) comprises three species: R. pumilio Peters, 1865, R. fi scherae Carter, 1966 and R. alethina Handley, 1966. Only the fi rst two species have been cytogenetically studied to date. Previous studies on specimens of Rhinophylla fi scherae from two populations from East of Andes (Colombia) showed the karyotype with 2n=34 and FN=56. In this paper, we report the results of cytogenetic analysis of six specimens of Rhinophylla fi scherae from B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…1b ). The results on G-, C-banding and Ag-NOR staining, FISH with telomeric and ribosomal DNA probes (not shown) are similar to those from literature [ 25 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…1b ). The results on G-, C-banding and Ag-NOR staining, FISH with telomeric and ribosomal DNA probes (not shown) are similar to those from literature [ 25 ].…”
Section: Resultssupporting
confidence: 88%
“…When comparing these results with Colombian RFI [ 28 ], the karyotype of Colombian RFI is similar to the RPU analyzed here, which emphasizes the differences between RFI of the two regions (Colombia and Brazil). These differences support the hypothesis that postulate the RFI from Brazil as a new species [ 25 ], Rhinophylla aff. fischerae , based on its reproductive isolation from the RFI of Colombia (due to multiple chromosomal rearrangements).…”
Section: Discussionsupporting
confidence: 87%
“…The Ag-NORs described here for the new karyotype of T. bidens were observed on the smallest pair of acrocentric chromosomes (pair 13). The constitutive heterochromatin found in the pericentromeric region of the chromosomes of T. bidens and in the pericentromeric and interstitial regions of some of the chromosomes of T. saurophila was consistent with the pattern observed in other studies of phyllostomine bats , MORIELLE-VERSUTE et al 1996, SANTOS et al 2001, SILVA et al 2005, BARROS et al 2009, GOMES et al 2010.…”
Section: Inversion?supporting
confidence: 90%
“…The genus Carollia has two karyomorphs: 2n=20/21 with a multiple sex chromosome system (XX/XY 1 Y 2 ), observed in most species ( Yonenaga et al 1969 , Pathak et al 1973 , Stock 1975 , Baker 1979 , Varella-Garcia et al 1989 , Pieczarka et al 2005 ), and 2n=22 with simple sex chromosome system found only in Carollia benkeithi Solari & Baker, 2006. On the other hand, the genus Rhinophylla has diversified karyotypes with four karyomorphs for Rhinophylla pumilio ( Tables 1 and 2 ) and two for Rhinophylla fischerae ( Baker and Bleier 1971 , Baker 1979 , Baker et al 1987 , Gomes et al 2010 ). No karyotype has been described for Rhinophylla alethina .…”
Section: Introductionmentioning
confidence: 99%